Beliefs negatively mediate adolescents’ and adults’ knowledge about sickle cell disease prevention and relationship choices; a one-center exploratory study in Central Region, Ghana - Godfred Kiteinkwa Laar; Justine Mwinbeku; Ebenezer Allotey Pappoe; Emmanuella Obike; Elizabeth Ankomah; Belinda Baidoo; Diana Baaba Morrison; Joseph Boachie; Patrick Adu (Archives of Public Health, 2024)
Abstract Background Sickle cell disease (SCD) is a common monogenic inheritable condition in sub-Saharan Africa. 30% of Ghanaians are estimated to be carriers creating a condition for stable SCD penetrance. Being inheritable, SCD is scientifically preventable through intentional spousal selection. This study therefore explored young adults’ knowledge, beliefs and prevention strategies regarding SCD. Methods This exploratory study employed a mixed-methods approach (semi-structured questionnaires and focus group discussion [FGD]) to explore the SCD knowledge and beliefs of participants (15–49 years). The data collection was intentionally sequential; initial administration of 386 questionnaires and then followed by the FGD (16 participants). FGD was thematically analysed whereas quantitative data was explored using structural equation modeling (SEM); p < 0.05 was considered statistically significant under two-tailed assumptions. Results Whereas 98.7% reported having heard about SCD, < 50% got the information through formal education. Overall, 49.7% knew their respective SCD status; the proportion increased with age (48.8% in < 30 years vs 64.4% in ≥ 30 years old), or higher degree status (48.8% in undergraduates vs 67.4% in postgraduates). Moreover, whereas nine-in-ten correctly identified that SCD is hereditable, three-in-ten believed that having a SCD child was a matter of fate. Our FGD revealed that whereas curses, and spiritual attack were misconceived as potential causes of SCD, stigmatization associated with SCD was a major concern. The SEM demonstrated that one’s knowledge about SCD prevention is significantly positively associated with relationship choices (b = 0.757, p < 0.05). Also, a participant’s knowledge about SCD preventive strategies was significantly associated with the individual’s beliefs about SCD (b = 0.335; p < 0.05). However, a participant’s SCD beliefs negatively mediated SCD preventive strategies-relationship choices association. Conclusions SCD beliefs likely transform linear quantitative associations into a complex non-linear interaction; public health campaigns ought to unearth and address SCD beliefs to maximize achieving the intended targets.